Theoretical basis for nursing - McEwen, Melanie; Wills, Evelyn M. (Philadelphia : Wolters Kluwer, 2019)
Enhance clinical practice with a clear understanding of nursing theory. Access the essential information you need to understand and apply theory in practice, research, education, and administration/management. The most concise and contemporary nursing theory resource available, Theoretical Basis for Nursing, 5th Edition, clarifies the application of theory and helps you become a more confident, well-rounded nurse. This acclaimed text is extensively researched and easy to read, giving you an engaging, approachable guide to developing, analyzing, and evaluating theory in your nursing career.
Philosophy, science, and nursing / Melanie McEwen -- Overview of theory in nursing / Melanie McEwen -- Concept development : clarifying meaning of terms / Evelyn M. Wills and Melanie McEwen -- Theory development : structuring conceptual relationships in nursing / Melanie McEwen -- Theory analysis and evaluation / Melanie McEwen -- Overview of grand nursing theories / Evelyn M. Wills -- Grand nursing theories based on human needs / Evelyn M. Wills -- Grand nursing theories based on interactive process / Evelyn M. Wills -- Grand nursing theories based on unitary process / Evelyn M. Wills -- Introduction to middle range nursing theories / Melanie McEwen -- Overview of selected middle range nursing theories / Melanie McEwen -- Evidence-based practice and nursing theory / Evelyn M. Wills and Melanie McEwen -- Theories from the sociologic sciences / Joan Engebretson -- Theories from the behavioral sciences / Melanie McEwen and Sattaria Smith Dilks -- Theories from the biomedical sciences / Melanie McEwen -- Ethical theories and principles / Cathy Rozmus and Jeffrey Spike -- Theories, models, and frameworks from leadership and management / Melinda Granger Oberleitner -- Learning theories / Evelyn M. Wills and Melanie McEwen -- Application of theory in nursing practice / Melanie McEwen -- Application of theory in nursing research / Melanie McEwen -- Application of theory in nursing administration and management / Melinda Granger Oberleitner -- Application of theory in nursing education / Melanie McEwen and Evelyn M. Wills -- Future issues in nursing theory / Melanie McEwen.
Includes bibliographical references and indexes.
Keywords: Nursing theory